FORMULASI DAN UJI STERILITAS SEDIAAN KRIM EKSTRAK DAUN RAMANIA (Bouea macrophylla Griffith) - Mukti, Yusuf Anggoro; Aryzki, Saftia; Ramadina, Najwa; Adawiyah, Rabiatul (Jurnal Farmasi & Sains Indonesia, 2025)
This study focuses on the formulation and evaluation of a cream based on Ramania leaf extract (Bouea macrophylla Griffith), known for its anti-inflammatory, antioxidant, and antimicrobial properties. The aim of the study is to develop an effective topical cream using different concentrations of Ramania leaf extract. Two different formulations were prepared and evaluated through various tests, including organoleptic evaluation, spreadability, adhesiveness, pH, homogeneity, viscosity, and stability. An experimental method was employed to determine the optimal formulation. The results showed that formulations 1 and 2, containing 5% and 6% Ramania leaf extract, demonstrated the best characteristics, including a homogeneous semi-solid texture, appropriate pH, sufficient adhesiveness, and optimal spreadability. These findings suggest that the Ramania leaf extract cream has the potential to be used as a topical product with good stability and potential therapeutic benefits. Keywords: Ramania leaf extract, topical cream, formulation evaluation.